Improving Cultural Arts Learning Outcomes In Dance Arts Material Using the Demonstration Method - Heryani, Usi Juwita; Maulidina, Maharani; Elvira, Ranti; Marwa, Marwa; Famella, Shelvie; Wahyuni, Sri (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
This research aims to improve student learning outcomes by using the demonstration method in learning dance at SMP Negeri 1 Siak. The type of research used is classroom action research (PTK) which is carried out in two cycles. The instrument of this research is an observation sheet, post test cycle, and test Skills. Data collection techniques were carried out by means of observation, literature study and documentation. Data were analyzed using a percentage formula. The research results showed that the demonstration method could improve the learning outcomes of class VIII.2 students at SMP Negeri 1 Siak in the Arts and Culture subject. This is shown by the results of the average percentage of student learning outcomes in cycle I being 68% with quite good criteria. After making improvements in cycle II, the average student learning activity increased by 91% with very good criteria. Based on the results of interviews and observations, there are several factors that cause the demonstration method to improve cultural arts learning outcomes in dance material, including: movement visualization, direct interaction, kinesthetic learning, muscle memory development, motivation and inspiration, and direct adjustments.